Empirical study of intellectual capital development in Singapore. - Chan, Ping Theng. (2008)
In this new economic era, manpower is increasing regarded as a source of wealth. Beyond this leveaging knowledge, creativity and innovation, firms must acquire infrastructure to retain the Intellectual Capital (IC) wealth in the organisation to create super-value.Our analysis seeks to find out similiarities and differences between the different treatment of IC among three main industries (Manufacturing, Commerce and Finance) in Singapore. We also seek to find out how the treatment of IC differs among Singapore firms of differing levels of knowledge intensity.